2015
DOI: 10.1016/j.otsr.2014.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Sequelae of pediatric osteoarticular infection

Abstract: The epidemiology and diagnosis of osteoarticular infections (OAI) have changed considerably in recent years, partly due to the development of molecular biology. Kingella kingae is now recognized as the most frequent pathogen in children under 4 years of age, while methicillin-resistant Staphylococcus aureus (SA) has been increasingly reported. Although the clinical course of OAI is mostly benign, with shorter antibiotic regimens and simplified treatments, serious functional impairments and life-threatening com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 42 publications
0
47
0
2
Order By: Relevance
“…Therapeutic delay is considered an important risk factor of sequelae, a 4-day delay has been suggested as acceptable in the treatment of uncomplicated osteomyelitis. [16] In this series, the average delay time was 14.9 days, only 7 patients (13.5%) had delay time for less than 4 days. Most patients sought treatment too late, when significant damage to bone and epiphysis had already happened, even surgical drainage could not change the final outcomes.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Therapeutic delay is considered an important risk factor of sequelae, a 4-day delay has been suggested as acceptable in the treatment of uncomplicated osteomyelitis. [16] In this series, the average delay time was 14.9 days, only 7 patients (13.5%) had delay time for less than 4 days. Most patients sought treatment too late, when significant damage to bone and epiphysis had already happened, even surgical drainage could not change the final outcomes.…”
Section: Discussionmentioning
confidence: 73%
“…The low recovery rate of hip may be attributed to the relative narrow space of the hip joint and the special blood supply of the femoral head, which will potentially predispose the joint capsular and the vascularization of the femoral head to be destroyed by the hyper pressure in the hip joint, subsequently leading to dislocation of the hip and AVN of the femoral head. [16] Thus, we recommend surgery for septic arthritis of the hip, even if the delay time is more than 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…2 Although the clinical course of osteitis is mostly benign, functional impairments can still occur. 3 Newborns have a greater risk of orthopedic sequelae, which need to be detected and treated early. 3 The main sequelae of osteitis are angular limb deformity because of partial growth arrest, and lower limb discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…3 Newborns have a greater risk of orthopedic sequelae, which need to be detected and treated early. 3 The main sequelae of osteitis are angular limb deformity because of partial growth arrest, and lower limb discrepancy. 3 In Finland, BCG vaccination of newborns was included in the national vaccination program from 1941 to 2006, and the coverage of the vaccinations was nearly 100%.…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus aureus ( S. aureus ) was chosen as the bacterial agent in this study, because it is a common pathogen found in osteomyelitis cases [31, 32]. The antibacterial activity against S. aureus (ATCC 6538) was tested using an agar diffusion assay (n=3/group), which was aerobically cultivated in Brain Heart Infusion (BHI) broth supplemented with 5 g yeast extract/L at 37°C.…”
Section: Methodsmentioning
confidence: 99%